The incidence risk of breast and gynecological cancer by antidepressant use: A systematic review and dose–response meta-analysis of epidemiological studies involving 160,727 patients - Zhuang, Yanjia; Pang, Xiaogang; Qi, Yuchen; Zhang, Tianshu; Cao, Guimao; Xue, Heming; Xu, Yifan; Xie, Shuoxin; Liu, Yifan; Wang, Yinuo; Li, Yunxiao; Xiong, Ying; et al. (Frontiers in Oncology, 2022)
Abstract Background and Objective: Antidepressant is widely prescribed to treat depression and anxiety disorders that may become chronic conditions among women. Epidemiological studies have yielded inconsistent results on the correlation between antidepressant use and the incidence risk of female breast and gynecological cancer, along with uncertain dose-response relationship. Therefore, we performed a systematic review and dose-response meta-analysis to investigate the association. Methods: Web of Science, Embase, PubMed, The Cochrane Library, and PsycINFO were systematically searched in Jan 2022, with no language limits. Random-effects models were used to calculate pooled effect sizes and 95% confidence intervals between studies. Linear and non-linear dose-response analyses were performed to evaluate the dose or duration of antidepressant use affecting the incidence risk of female breast and gynecological cancer, and further subgroup analyses were systematically performed with stratifying by almost all study characteristics and important potential confounders, in order to further clarify and validate the important potential hypotheses regarding the biological mechanism underlying this association. Results: Based on a systematic literature search, 34 eligible studies (27 case-control studies and 7 cohort studies) involving 160727 female breast and gynecological cancer patients found that antidepressant use didn't increase the incidence risk of female breast and gynecological cancer(pooled OR: 1.01; 95% CI: 0.97, 1.04, I² = 71.5%, P < 0.001), and even decreased the incidence risk of ovarian cancer(pooled OR: 0.91; 95% CI: 0.83, 1, I² = 17.4%, P = 0.293), along with a non-linear dose-response relationship(P non-linearity < 0.05) between the duration of antidepressant use and incidence risk of female breast cancer, another inverse linear dose-response association existed for gynecological cancer, specifically when an increase of cumulative defined daily dose or duration to a high level, like 25550 doses(OR 0.91, 95% CI 0.85–0.98, P linearity < 0.05) or 4380 days(OR: 0.82; 95%CI: 0.7, 0.96, P linearity < 0.05), compared to non-users. Conclusion: This systematic review and dose-response meta-analysis found that antidepressant use did not increase the incidence risk of female breast and gynecological cancer and even decreased the incidence risk of ovarian cancer, along with a non-linear or linear dose-response relationship.